2012
DOI: 10.1177/1753193412458646
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 5-fluorouracil on flexor tendon healing by using a biodegradable gelatin, slow releasing system: experimental study in a hen model

Abstract: This study investigated the effects of 5-fluorouracil in a slow-release biodegradable gelatin system on tendon healing. Gelatin blocks prepared in a size of 10 × 20 × 1 mm were loaded with 10, 20, and 30 mg of 5-fluorouracil, and 30 adult white Leghorn chickens were used. The tendons to the third and fourth toes were severed and repaired. The extremities were casted for three weeks. After sacrifice, the tendons were examined histologically and biomechanically for adhesion formation. The 10 mg-loaded gelatin gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…The dosage used ranged from 1 mg/mL to 50 mg/mL of 5FU topically to repaired tendons. Nearly all studies used 5 minute exposures expect for Karaaltin et al 11 who wrapped slow‐releasing biodegradable gelatin infused‐5‐FU blocks to the repaired tendons. The details of these articles have been summarized in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dosage used ranged from 1 mg/mL to 50 mg/mL of 5FU topically to repaired tendons. Nearly all studies used 5 minute exposures expect for Karaaltin et al 11 who wrapped slow‐releasing biodegradable gelatin infused‐5‐FU blocks to the repaired tendons. The details of these articles have been summarized in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that similar outcomes would be able to be replicated with similar ease. Of note Karaaltin et al 11 in their 2013 study involving 5FU gelatin‐infused blocks reported significantly higher inflammation at the higher dosing levels of 20 and 30 mg/mL. Of importance however is that this study was the one to use 5FU gelatin‐infused blocks rather than the 5‐minute “single touch” technique adopted by the other nine studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results generally agree with those of the biomechanical studies conducted by Karaaltin et al . [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…Further strategies are based on the use of agents that limit cellular proliferation by preventing DNA replication, thus preventing fibroblasts from expanding and forming adhesions. Agents that present these characteristics include mitomycin-C, which has been demonstrated to reduce adhesions in a rabbit pericardial model [111], or 5-fluoroacil, which also reduced adhesions in the flexor tendon in chickens [112]. However, the side effects of these drugs still represent a crucial limitation for their use as antiadhesive agents.…”
Section: Antiadhesive Agentsmentioning
confidence: 99%